2005
DOI: 10.1007/s11064-005-2686-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Action of Hypothalamic Peptide PRP-1 at Various Time Survivals Following Spinal Cord Hemisection

Abstract: The purpose of the present study was to evaluate the neuroprotective action of proline-rich peptide-1 (PRP-1) produced by hypothalamic nuclei cells (nuclei paraventricularis and supraopticus) following lateral hemisection of spinal cord (SC). The dynamics of rehabilitative shifts were investigated at various periods of postoperative survival (1-2, 3, and 4 weeks), both with administration of PRP-1 and without it (control). We registered evoked spike flow activity in both interneurons and motoneurons of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…This cytokine is also a mediator of the hypothalamus-neurohypophysis-bone marrow axis and a powerful immunomodulator [1,2]. Strong antibacterial (in vivo) and antiviral (in vitro) properties of hypothalamic proline rich peptides [3], anti neurodegenerative effects [4] and immunotropic properties [5] provide evidence for the existence of brain protective mechanisms against infection, neurodegeneration, immunodefficiencies [6] and tumors [7,8,[11][12][13]. We demonstrated that PRP-1 induced decay of tumor cells L929 and decreased mitotic activity of transformed mouse fibroblast cells, dose response growth inhibition of Jurkat cells, and inhibition of lymphosarcoma in vivo [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This cytokine is also a mediator of the hypothalamus-neurohypophysis-bone marrow axis and a powerful immunomodulator [1,2]. Strong antibacterial (in vivo) and antiviral (in vitro) properties of hypothalamic proline rich peptides [3], anti neurodegenerative effects [4] and immunotropic properties [5] provide evidence for the existence of brain protective mechanisms against infection, neurodegeneration, immunodefficiencies [6] and tumors [7,8,[11][12][13]. We demonstrated that PRP-1 induced decay of tumor cells L929 and decreased mitotic activity of transformed mouse fibroblast cells, dose response growth inhibition of Jurkat cells, and inhibition of lymphosarcoma in vivo [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This cytokine is also a mediator of hypothalamus-neurohypophysis-bone marrow axis as well as a powerful immunomodulator [1,2]. Strong antibacterial (in vivo) and antiviral (in vitro) properties of hypothalamic proline rich peptides [3] as well as antineurodegenerative [4] and their immunotropic properties [5] provide evidence for the existence of brain protective mechanisms against infection, neurodegeneration, immunodeficiencies [6] and tumor. We demonstrated that PRP-1 induced decay of tumor cells L929 and decreased mitotic activity of those transformed mouse fibroblast cells [1,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of interleukin secretion by hypothalamic magnocellular nuclei as well as biosynthesis of a new class cytokines (PRPs) illustrate the capability of the brain neuroendocrine cells synthesize cytokines along with vasopressin, oxytocin and organotropic (cardioactive) neurohormones. Strong antibacterial (in vivo) and antiviral (in vitro) properties of hypothalamic proline rich peptides [3] as well as antineurodegenerative [4] and their immunotropic properties [5,6] provide evidence for the existence of brain protective mechanisms against infection, neurodegeneration, immunodeficiencies [6] and tumor [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%